Development and pharmacological characterization of a model of sleep disruption-induced hypersensitivity in the rat - Wodarski, Rachel; Schuh-Hofer, Sigrid; Treede, Rolf-Detlef (European journal of pain, 2015)
Background: Sleep disturbance is a commonly reported co-morbidity in chronic pain patients, and conversely, disruption of sleep can cause acute and long-lasting hypersensitivity to painful stimuli. The underlying mechanisms of sleep disruption-induced pain hypersensitivity are poorly understood. Confounding factors of previous studies have been the sleep disruption protocols, such as the ‘pedestal over water’ or ‘inverted flower pot’ methods, that can cause large stress responses and therefore may significantly affect pain outcome measures. Methods: Sleep disruption was induced by placing rats for 8 h in a slowly rotating cylindrical cage causing arousal via the righting reflex. Mechanical (Von Frey filaments) and thermal (Hargreaves) nociceptive thresholds were assessed, and plasma corticosterone levels were measured (mass spectroscopy). Sleep disruption-induced hypersensitivity was pharmacologically characterized with drugs relevant for pain treatment, including gabapentin (30 mg/kg and 50 mg/kg), Ica-6p (Kv7.2/7.3 potassium channel opener; 10 mg/kg), ibuprofen (30 mg/kg and 100 mg/kg) and amitriptyline (10 mg/kg). Results: Eight hours of sleep disruption caused robust mechanical and heat hypersensitivity in the absence of a measurable change in plasma corticosterone levels. Gabapentin had no effect on reduced nociceptive thresholds. Ibuprofen attenuated mechanical thresholds, while Ica-6p and amitriptyline attenuated only reduced thermal nociceptive thresholds. Conclusions: These results show that acute and low-stress sleep disruption causes mechanical and heat hypersensitivity in rats. Mechanical and heat hypersensitivity exhibited differential sensitivity to pharmacological agents, thus suggesting dissociable mechanisms for those two modalities. Ultimately, this model could help identify underlying mechanisms linking sleep disruption and hypersensitivity.
Gesehen am 20.11.2017